2020
DOI: 10.1101/2020.08.11.20172841
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Progressive changes in glutamate concentration in early stages of schizophrenia: A longitudinal 7-Tesla MRS study

Abstract: Progressive reduction in glutamatergic transmission has been proposed as an important component of the illness trajectory of schizophrenia. Despite its popularity, to date, this notion has not been convincingly tested in patients in early stages schizophrenia. In a longitudinal 7T magnetic resonance spectroscopy (1H-MRS), we quantified glutamate at the dorsal anterior cingulate cortex in 21 participants with a median lifetime antipsychotic exposure of less than 3 days and followed them up after 6 months of tre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 55 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…This result suggests that findings of reduced Glu levels in patients compared with healthy volunteers are not associated with accelerated aging in patients but may be explained by greater antipsychotic exposure, although lower Glu levels have been reported in minimally treated patients with first-episode psychosis. 80,81 This finding may explain reports of reduced anterior cingulate cortex Glu levels in patients with chronic schizophrenia compared with healthy volunteers. 9-14 Indeed, a large longitudinal study reports a decrease in Cr-scaled Glu levels with treatment.…”
Section: Discussionmentioning
confidence: 75%
“…This result suggests that findings of reduced Glu levels in patients compared with healthy volunteers are not associated with accelerated aging in patients but may be explained by greater antipsychotic exposure, although lower Glu levels have been reported in minimally treated patients with first-episode psychosis. 80,81 This finding may explain reports of reduced anterior cingulate cortex Glu levels in patients with chronic schizophrenia compared with healthy volunteers. 9-14 Indeed, a large longitudinal study reports a decrease in Cr-scaled Glu levels with treatment.…”
Section: Discussionmentioning
confidence: 75%
“…One study reported higher levels 28 , whereas others found reductions [29][30][31] or no significant differences 32,33 in first-episode psychosis or schizophrenic patients in the ACC. The same irregularity can be found for subjects at risk for psychosis, in the ACC higher 4,11,[34][35][36] and lower 10 glutamate levels, or even no significant results [37][38][39] have been described.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 95%
“…To our knowledge, only 2 studies report on longitudinal GSH measurements in psychosis to date. In a sample of 21 subjects with first episode schizophrenia scanned at baseline with <3 days of lifetime antipsychotic exposure and followed after 6 months of antipsychotic treatment, GSH levels were highly stable (Mean(SD) at baseline =1.71 (0.36), at 6-months = 1.75 (0.23)) [84]. The same stability in GSH levels was also seen in the 10 demographically healthy controls scanned at 2 time points (Mean(SD) at baseline =1.64 (0.25), at 6-months = 1.63 (0.32)) [84].…”
Section: Intracortical Gsh In Schizophrenia: Mrs Studiesmentioning
confidence: 99%
“…In a sample of 21 subjects with first episode schizophrenia scanned at baseline with <3 days of lifetime antipsychotic exposure and followed after 6 months of antipsychotic treatment, GSH levels were highly stable (Mean(SD) at baseline =1.71 (0.36), at 6-months = 1.75 (0.23)) [84]. The same stability in GSH levels was also seen in the 10 demographically healthy controls scanned at 2 time points (Mean(SD) at baseline =1.64 (0.25), at 6-months = 1.63 (0.32)) [84]. In a larger sample of 38 patients with first episode psychosis (onset within 2 years) and 48 healthy controls followed up over 4 years [85], GSH levels was found to have a near zero change in all 5 studied brain regions (ACC, thalamus, DLPFC, centrum semiovale and orbitofrontal cortex) over time, strongly arguing for a 'trait-like' stability of GSH levels compared to other metabolites.…”
Section: Intracortical Gsh In Schizophrenia: Mrs Studiesmentioning
confidence: 99%
See 1 more Smart Citation